Poly-ε-Caprolactone-Hydroxyapatite-Alumina (PCL-HA-α-Al2O3) Electrospun Nanofibers in Wistar Rats - Ruiz Ramírez, Luis Roberto; Donohue-Cornejo, Alejandro; Espinosa Cristobal, Leon Francisco; Farias, Rurik; Martinez, Carlos Alberto; Reyes-López, Simón Yobanny; Alvarez Ortega, Oskar (2022)
Biodegradable polymers of natural origin are ideal for the development of processes in tissue engineering due to their immunogenic potential and ability to interact with living tissues. However, some synthetic polymers have been developed in recent years for use in tissue engineering, such as Poly-"-caprolactone. The nanotechnology and the electrospinning process are perceived to produce biomaterials in the form of nanofibers with diverse unique properties. Biocompatibility tests of poly-"-caprolactone nanofibers embedded with hydroxyapatite and alumina nanoparticles manufactured by means of the electrospinning technique were carried out inWistar rats to be used as oral dressings. Hydroxyapatite as a material is used because of its great compatibility, bioactivity, and osteoconductive properties. The PCL, PCL-HA, PCL- -Al2O3, and PCL-HA- -Al2O3 nanofibers obtained in the process were characterized by infrared spectroscopy and scanning electron microscopy. The nanofibers had an average diameter of (840 230) nm. The nanofiber implants were placed and tested at 2, 4, and 6 weeks in the subcutaneous tissue of the rats to give a chronic inflammatory infiltrate, characteristic foreign body reaction, which decreased slightly at 6 weeks with the addition of hydroxyapatite and alumina ceramic particles. The biocompatibility test showed a foreign body reaction that produces a layer of collagen and fibroblasts. Tissue loss and necrosis were not observed due to the coating of the material, but a slight decrease in the inflammatory infiltrate occurred in the last evaluation period, which is indicative of the beginning of the acceptance of the tested materials by the organism.